The impact of state intervention on "underperforming" schools in Massachusetts: Implications for policy and practice. - McQuillan, Patrick J.; Salomon-Fernandez, Yves (Education Policy Analysis Archives, 2008)
Since passage of the federal No Child Left Behind Act (NCLB) in 2002, statedepartments of education across the U.S. have been busy creating or modifying school accountability systems to meet NCLB guidelines. Ultimately, NCLB seeks to have all public school students proficient in English/Language Arts and mathematics by 2014. To identify schools in danger of not meeting this goal, states must establish student performance benchmarks and identifyschools not making adequate yearly progress (AYP). Those consistently failing to make AYP can be ordered into "radical restructuring," which may include having the state intervene in running the school (U. S. Department of Education, 2002). Given these NCLB provisions and the growing number of schools not meeting AYP, the number of state interventions in low-performingschools will certainly increase. Accordingly, this article explores two questions about state-led interventions. First, how have teachers and administrators in underperforming schools in Massachusetts perceived state intervention? In addition, based on their perceptions, what might be done to make the process more effective? At three schools that experienced interventions from the Massachusetts Department of Education, a qualitative study explored the process of state intervention. A survey to principals in22 of the 23 schools deemed underperforming by the state between 2000 and 2004 supplemented the in-depth qualitative work. Drawing on these mixed methods data sources, this article offers a series of proposals aimed at informing future state interventions in Massachusetts and elsewhere.